New Insights on Bone Tissue and Structural Muscle-Bone Unit in Constitutional Thinness - Bailly, Mélina; Boscaro, Audrey; Thomas, Thierry; Féasson, Léonard; Costes, Frédéric; Pereira, Bruno; Hager, Jorg; Estour, Bruno; Galusca, Bogdan; Metz, Lore; Courteix, Daniel; Thivel, David; et al. (Frontiers in Physiology, 2022)
While few studies pointed out low bone mineral densities in constitutionally thin women, little is known about potential explanations. The objective was to further explore bone architecture in both women and men with constitutional thinness to investigate their mechanical muscle-bone coupling (or uncoupling). Thirty constitutionally thin people and 31 normal weight controls participated in the study. Body composition, hip structural analysis, and trabecular bone score were assessed by dual-energy X-ray absorptiometry, bone architecture using high-resolution peripheral quantitative computed tomography, and muscle explorations through histological staining on muscle biopsies. Thirty-two out of the 48 indexes relative to density, geometry, texture, and architecture of bones were found significantly lower (p < 0.05) in constitutionally thin individuals compared with controls. This observation was particularly pronounced in constitutionally thin men. Bone microarchitecture was more altered in weight-supporting bone (tibia) than in non-weight supporting (radius) bone, which might refer to a normal physiological adaptation (Frost’s mechanostat theory). Yet, the heat-maps of correlations analyses showed many alterations of body weight or muscle associations with bone parameters in constitutionally thin individuals contrary to controls. Present results might support the idea of intrinsic disturbances of bone cells independently to the small muscle structure, particularly in men.